Secure two-way relaying with successive interference cancellation and fountain codes: performance analysis - Nguyen Thi Hau; Tran Trung Duy (Universitas Ahmad Dahlan, 2026)
This paper proposes a secure two-way relaying (TWR) scheme using fountain codes (FCs), successive interference cancellation (SIC), and digital network coding (DNC). Using FCs, two sources exchange their data by first encoding the data into a series of packets (called encoded packets). These encoded packets are then exchanged between the sources via the help of a common relay, and they are also overheard by an eavesdropper. The packet exchange is carried out over two time slots: i) in the first time slot, both sources send their encoded packets to the rela y; and ii) the relay applies SIC to decode two received packets, and then broadcasts the exclusive OR (XORed) packet to both sources in the second time slot. The sources and the eavesdropper try to collect a sufficient number of encoded packets to successfully recover the original data. This paper derives and validates exact closed-form expressions for system throughput (TP), system outage probability (SOP), and system intercept probability (SIP) over Rayleigh fading channels. Furthermore, our findings reveal a reliability-security trade-off as well as the impact of system parameters on the network performance.